Synthesis of fully degradable cationic polymers with various topological structures via postpolymerization modification by using thio-bromo "click" reaction. Issue 17 (12th April 2021) - Dai, Yunkai; Hu, Zhitao; Wang, Xiaoying; Liu, Xingliang; Li, Yuanchao; Shi, Yi; Chen, Yongming
Abstract : Poly(ε-caprolactone) (PCL) based and fully degradable cationic polymers with various topological structures and tunable charge densities were prepared via postpolymerization modification using thio-bromo "click" chemistry. Abstract : Synthesis of cationic polymers possessing significant therapeutic potential is of tremendous research interest. Here, we report a facile synthesis of poly(ε-caprolactone) (PCL) based cationic polymers with controlled topological structures and tunable charge densities via postpolymerization modification using thio-bromo "click" chemistry. Three types of polymeric precursors were prepared by ring-opening polymerization (ROP) or combination of ROP and azide–alkyne click reaction, including linear homopolymer poly(α-bromo-ε-caprolactone) (P(CL-Br)), block copolymer PCL- b -P(CL-Br), and bottlebrush polymer PCL- g -(PCL- b -P(CL-Br)), and then the P(CL-Br) blocks or segments were modified using the thio-bromo click reaction with a thiol bearing a tertiary amino group, yielding the corresponding cationic polymers, respectively. Size exclusion chromatography (SEC) and 1 H NMR characterization demonstrated successful synthesis of the cationic polymers with controlled molecular weights and topological structures that may have great potential for biomedical applications.